THE EVALUATION OF PAIN CHARACTERISTICS OF PATIENTS WITH OSTEOPOROSIS - Güneş Yavuzer; Serpil Savaş; Haydar Gök; Gülay Dinçer; Peyman Yalçın (Archives of Rheumatology, 2001)
The most leading symptom of patients with osteoporosis is chronic pain, due to repeated microfractures. In this study, in order to help to differentiate the diagnosis of back pain, the pain characteristics of 40 osteoporotic patients and 40 non-porotic controls with the same age were compared. Pain duration, severity, localisation, radiation, aggrevating and relieving factors were assessed and no statistically significant difference was found between the groups. This result pointed that repeated fractures are not the only etiological factor for back pain, osteoarthritis, dysfunction of facet joints and disc pathologies are the common factors to initiate back pain for both of the groups.